Estudio de prefactibilidad para la instalación de una planta elaboradora de mermelada con fruta confitada a base de frutas exóticas para el mercado limeño - Matsubara Bautista, Akira Diego (2018)
For the investment project of a processing plant of exotic fruit jam with candied fruit, it was determined that product will be for the population residing in Metropolitan Lima of socioeconomic levels A and B that have an affinity for gourmet products and in the age range of 18-70 years. This demand would have a value to the last year of the project of 950 296 bottles of 350gr. The location of the plant will take place in the department of Lima, because it is close to the target market, and will be located in the district of Comas, due to the low cost of the land. In the engineering of the project, the number of machines necessary to carry out the production process of the jams was determined, as well as the number of operators who were considered the degree of saturation, having a total of 10 workers. In addition, it was determined that the production area required an area of 337 m2 and that the plant would have a total of 1 000 m2. The administrative organization will be composed of 5 managements that will control the areas of Production, Logistics, Commercial and Marketing, Finance and Human Resources, who will have formed within their teams Heads of Area, Executives and analysts. All the managements will be under the supervision and control of the General Manager. Finally, the financial evaluation showed that the project is viable due to the good rates of return that are obtained from the discounted cashflows. Likewise, under the capital structure, payment and receivables policy of the company, a good management of the cash flow of the company is obtained. In addition, the project will contribute to social development due to the retro productivity that it generates through the generation of employment and tax benefits, which will help for the realization of social works by the state.